2007
DOI: 10.1002/adsc.200600313
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stabilization of Genetically Modified Penicillin G Acylase in the Presence of Organic Cosolvents by Co‐ Immobilization of the Enzyme with Polyethyleneimine

Abstract: Penicillin G acylase (PGA) is an enzyme that hardly interacts with polycationic polymers (e.g., polyethyleneimine, PEI) and thus the enzyme cannot be stabilized against the action of organic solvents by its co-immobilization with the polymer in the same support, neither covalently attached to the support nor adsorbed on the already immobilized enzyme. However, a new mutant PGA bearing eight additional Glu residues homogenously distributed throughout the enzyme surface may interact with the polymer. The co-immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Desimone et al [12] reported that the tolerance of sol-gel-immobilized Saccharomyces cerevisiae is correlated with the log K ow value of the solvent, and it increases with the increase in the value. It has been shown that this hydrophilic microenvironments performed by immobilization improved stabilization of enzymes in the presence of organic co-solvents [15,41,59]. The authors suggested that these micro-environments seems to be very useful not only to reduce the concentration of cosolvent existing microenvironment of the enzyme molecule, but also to prevent the direct interaction between the enzyme surface and a potentially harmful reaction medium as organic solvents and supercritical fluids.…”
Section: Phenol Degradation By Free and Immobilized Cells Of A Pullumentioning
confidence: 95%
“…Desimone et al [12] reported that the tolerance of sol-gel-immobilized Saccharomyces cerevisiae is correlated with the log K ow value of the solvent, and it increases with the increase in the value. It has been shown that this hydrophilic microenvironments performed by immobilization improved stabilization of enzymes in the presence of organic co-solvents [15,41,59]. The authors suggested that these micro-environments seems to be very useful not only to reduce the concentration of cosolvent existing microenvironment of the enzyme molecule, but also to prevent the direct interaction between the enzyme surface and a potentially harmful reaction medium as organic solvents and supercritical fluids.…”
Section: Phenol Degradation By Free and Immobilized Cells Of A Pullumentioning
confidence: 95%
“…The development of biocatalysts is necessary to make the production of 6-APA economically feasible. Nowadays, technologies have been focused on modification of carriers [4] and immobilization techniques [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the enzymatic method exhibited promising application potential for the chemoenzymatic production of cefathiamidine. However, many problems associated with this enzymatic process such as relatively low substrate concentrations and unsatisfactory operational stability for its large-scale application may be addressed by the corresponding measures (e.g., using the supersaturated substrate solutions and fed-batch feeding strategy, and improving enzyme immobilization methods) (Volpato et al 2010; Ferreira et al 2007; Youshko et al 2004; Illanes et al 2007; Montes et al 2007). …”
Section: Discussionmentioning
confidence: 99%